1995
DOI: 10.1021/jf00049a015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Protein Quality of Beefstock Bone Isolates for Use as an Ingredient in Meat and Poultry Products

Abstract: The total protein, amino acids including 4-hydroxyproline, and estimated connective tissue proteins of three processed beefstock bone isolates were determined as potentially useful indices for evaluating their protein quality. Variations in amino acid composition were found among all three batches of beefstock bone isolates investigated. The total protein of demineralized beefstock bone powders, as determined by amino acid analysis, varied (P < 0.05) and ranged from 78 to 80% on a dry weight basis. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…In their paper examining the quality of protein in bones from young bulls, Zarkadas et al (1995) reported that the content of total protein of demineralised bone powder varied between 78-80% in dry matter and connective tissue proteins accounted for 72.3-81.1%…”
Section: Resultsmentioning
confidence: 99%
“…In their paper examining the quality of protein in bones from young bulls, Zarkadas et al (1995) reported that the content of total protein of demineralised bone powder varied between 78-80% in dry matter and connective tissue proteins accounted for 72.3-81.1%…”
Section: Resultsmentioning
confidence: 99%
“…Laser-Reuterswä rd (1985). a Data taken from (a) Linder et al (1995a); (b) Eastoe and Leach (1977); (c) Zarkadas et al (1995); (d) Laser-Reuterswä rd (1985); (e) Eggum et al (1989).…”
Section: Protein Quality Indexesmentioning
confidence: 99%
“…They are a potential source of ingredients in various meat products (Laser-Reuterswärd et al, 1982). Data on amino acid composition of meat bone hydrolysates, isolates and meals have not been widely reported (Hegedüs et al, 1983(Hegedüs et al, , 1990Zarkadas et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there are some commercial collagen-based byproducts for use in the meat processing industry as ingredients in various meat products. Such collagen byproducts include skins (rind) and skin trimmings, tendon, beef shank, sinew residues, and hand or mechanically separated bones from beef, pork, and poultry carcasses (Zarkadas et al, 1995). However, high collagen content in meat products could produce physical defects during the cooking like unstable emulsions, formation of gelatin or fat pockets, or bad peeling (Flores, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…However, high collagen content in meat products could produce physical defects during the cooking like unstable emulsions, formation of gelatin or fat pockets, or bad peeling (Flores, 1980). In addition, the amount of collagen byproducts relates to the final product and nutritional qualities (Flores, 1980;Zarkadas et al, 1995).…”
Section: Introductionmentioning
confidence: 99%